Association of Dry Eye with Laryngopharyngeal Reflux in Clinical Practice. (1st February 2022) - Bonini, S.; Labetoulle, M.; Messmer, E.; Aragona, P.; Benitez Castillo, J. M.; Ciprandi, G.; Damiani, V.; Irkec, M.; Baudouin, C.; Rolando, M.
ABSTRACT: Background: Dry eye disease (DED) is a common disorder, accounting for up to 35% of the general population. Therefore, we hypothesized that laryngopharyngeal reflux (LPR), inducing refluxate rising into airways, may involve the ocular surface and may either induce or worsen DED. Aim: To investigate the prevalence and relevance of suspected LPR in DED patients and subjects with refractive problems (RP) without DED, they were defined as non-dry eye group (NEG) in clinical practice. Methods: This retrospective study included consecutive patients evaluated because of dry eye-like symptoms at eight tertiary ophthalmological clinics. Parameters included reflux symptom index (RSI), ocular surface disease index (OSDI), symptom assessment in dry eye (SANDE) for frequency and severity, Schirmer test, tear break-up time (BUT), and Oxford grading. Results: The study included 245 subjects (72.5% females; mean age 56.3 years), 152 DED patients, and 93 sex- and age-matched NEG subjects. Pathological RSI (score>13) was detected in 80 subjects (32.6%); 68 (85%) with DED and 12 (15%) CG (OR = 8; p < .0001). In NEG, pathological RSI was associated with higher SANDE (Frequency and Severity), OSDI, and Schirmer scores (OR = 16.36; 14.51; 12.54; and 7.22, respectively. In DED patients, pathological RSI was associated with higher OSDI values (OR = 8.75). Conclusion: Patients with DED are at eight times higher risk for having pathological RSI than NEG patients. Moreover, pathological RSI was associated with more severe ocular symptoms both in DED and non-DED patients. The role of LPR in definite DED patients remains to be clarified, but this condition deserves to be investigated in managing patients with DED symptoms.